Maternal and foetal outcomes in referred obstetric cases at a tertiary care centre in Lumbini Province, Nepal - Subedi, Jigyasa; KC, Tara; Sharma, Deepanjali; Lamsal, Manoj; Banu, Hasina; Thakur, Sabnam; Chaube, Vivek; Laxmi Manandhar, Bekha (Journal of Chitwan Medical College, 2025)
Introduction: An effective referral system is essential for ensuring continuity of obstetric care to prevent maternal morbidity and mortality. This study was conducted with an objective to find out reasons for obstetric referrals, maternal and perinatal outcome in a tertiary care centre of Nepal.  Method: This descriptive, cross-sectional study was conducted at Universal College of Medical Sciences Nepal, from 01 Oct 2021 to 31 Mar 2022. The study analysed obstetric referral cases, focusing on referral indications, clinical examinations, investigations, and interventions performed. Referred antenatal and intrapartum cases of gestational age ≥28 weeks who delivered at study centre was included. Postpartum cases, gestation